Sulfation of chondroitin and bile acids converges to antagonize Wnt/β-catenin signaling and inhibit APC deficiency-induced gut tumorigenesis - Pengfei Xu; Yue Xi; Jong-Won Kim; Junjie Zhu; Min Zhang; Meishu Xu; Songrong Ren; Da Yang; Xiaochao Ma; Wen Xie (Elsevier, 2024)
Sulfation is a crucial and prevalent conjugation reaction involved in cellular processes and mammalian physiology. 3'-Phosphoadenosine 5'-phosphosulfate (PAPS) synthase 2 (PAPSS2) is the primary enzyme to generate the universal sulfonate donor PAPS. The involvement of PAPSS2-mediated sulfation in adenomatous polyposis coli (APC) mutation-promoted colonic carcinogenesis has not been reported. Here, we showed that the expression of PAPSS2 was decreased in human colon tumors along with cancer stages, and the lower expression of PAPSS2 was correlated with poor prognosis in advanced colon cancer. Gut epithelial-specific heterozygous Apc deficient and Papss2-knockout (ApcΔgut-HetPapss2Δgut) mice were created, and the phenotypes were compared to the spontaneous intestinal tumorigenesis of ApcΔgut-Het mice. ApcΔgut-HetPapss2Δgut mice were more sensitive to gut tumorigenesis, which was mechanistically accounted for by the activation of Wnt/β-catenin signaling pathway due to the suppression of chondroitin sulfation and inhibition of the farnesoid X receptor (FXR)-transducin-like enhancer of split 3 (TLE3) gene regulatory axis. Chondroitin sulfate supplementation in ApcΔgut-HetPapss2Δgut mice alleviated intestinal tumorigenesis. In summary, we have uncovered the protective role of PAPSS2-mediated chondroitin sulfation and bile acids-FXR-TLE3 activation in the prevention of gut carcinogenesis via the antagonization of Wnt/β-catenin signaling. Chondroitin sulfate may be explored as a therapeutic agent for Papss2 deficiency-associated colonic carcinogenesis.